Multiwavelength observations of the γ-ray-emitting narrow-line Seyfert 1 PMN J0948+0022 in 2011. Issue 4 (28th January 2014) - D'Ammando, F.; Larsson, J.; Orienti, M.; Raiteri, C. M.; Angelakis, E.; Carramiñana, A.; Carrasco, L.; Drake, A. J.; Fuhrmann, L.; Giroletti, M.; Hovatta, T.; Max-Moerbeck, W.; et al.
Abstract: We report on radio-to-γ-ray observations during 2011 May–September of PMN J0948+0022, the first narrow-line Seyfert 1 (NLSy1) galaxy detected in γ-rays by Fermi -Large Area Telescope. Strong variability was observed in γ-rays, with two flaring periods peaking on 2011 June 20 and July 28. The variability observed in optical and near-infrared seems to have no counterpart in γ-rays. This different behaviour could be related to a bending and inhomogeneous jet or a turbulent extreme multicell scenario. The radio spectra showed a variability pattern typical of relativistic jets. The XMM spectrum shows that the emission from the jet dominates above ∼2 keV, while a soft X-ray excess is evident in the low-energy part of the X-ray spectrum. Models where the soft emission is partly produced by blurred reflection or Comptonization of the thermal disc emission provide good fits to the data. The X-ray spectral slope is similar to that found in radio-quiet NLSy1, suggesting that a standard accretion disc is present, as expected from the high accretion rate. Except for the soft X-ray excess, unusual in jet-dominated active galactic nuclei, PMN J0948+0022, shows all characteristics of the blazar class.